KEBIJAKAN FORMULATIF TENTANG TINDAK PIDANA PILKADA DALAM PERSPEKTIF PEMILIHAN KEPALA DAERAH YANG DEMOKRATIS DAN TRANSPARAN - Purnawan Dwikora Negara, Agus Sudaryanto dan (Jurnal Konstitusi, 2010)
The implementation of the article 18 verse (4) of the 1945 Constitution, namely the law no 32, 2004 on the Local Government, as changed in the law no.8, 2005 and the law no. 12, 2008, stipulate that the candidates of the local head and of the vice local head are elected in a couple through a direct local head election by the people, instead of by the Local House of Representative. In such elections, it is possible to occur deceitful practices or criminal acts, as regulated in the articles of 115-119 of the local government law. Therefore, it is necessary to understand about the existence of formulative policies on the head election as an anticipative step in realizing a democratic and transparent local head election.